2015
DOI: 10.1097/mco.0000000000000187
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal nutrient sensing and blood glucose control

Abstract: Targeting the intestinal nutrient-sensing machinery by dietary and/or pharmacological means holds promises in particular for treatment of type 2 diabetes. This interest may help to better understand the nutrient-sensing processes and the involvement of the intestine in overall endocrine, neuronal and metabolic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 58 publications
2
33
0
2
Order By: Relevance
“…Nonetheless, in recent studies it has also been found to exhibit paracrine and exocrine effects on pancreatic islet cells, leading to enhanced insulin secretion . The releases of both hormones are triggered by the presence of nutrients in the intestinal lumen, which is detected by membrane‐bound transporters found on enterocytes along the intestinal lining . In recent studies, SCFA receptors were found to be present in the distal gut and were associated with enhanced GLP‐1 and PYY secretion (Fig.…”
Section: Effects Of Resistant Starch Consumption Leading To Improved mentioning
confidence: 95%
“…Nonetheless, in recent studies it has also been found to exhibit paracrine and exocrine effects on pancreatic islet cells, leading to enhanced insulin secretion . The releases of both hormones are triggered by the presence of nutrients in the intestinal lumen, which is detected by membrane‐bound transporters found on enterocytes along the intestinal lining . In recent studies, SCFA receptors were found to be present in the distal gut and were associated with enhanced GLP‐1 and PYY secretion (Fig.…”
Section: Effects Of Resistant Starch Consumption Leading To Improved mentioning
confidence: 95%
“…(Liou et al 2011;Diakogiannaki et al 2013). The incretin hormones GLP-1 and GIP are of particular interest due to their insulinotrophic action and high potential for the treatment of metabolic disorders, such as diabetes or obesity (Zietek & Daniel, 2015). In the past decade, G-protein-coupled receptors, such as the free fatty acid receptors GPR40 and GPR120 or the bile acid receptor TGR5 , have been identified as intestinal sensors mediating gut hormone release.…”
Section: Transport For Sensingmentioning
confidence: 99%
“…Interestingly, Zietek and Daniel (2015) and Magro et al (2018) documented that the release of GLP‐1 has been increased as a compensatory mechanism to prevent the occurrence of hypoglycaemia in high‐risk IBD patients, such as active CD patients, who suffer from GLP‐2 blockade, nutrient malabsorption and chronic diarrhoea 28,29 …”
Section: Glucagon‐like Peptidesmentioning
confidence: 99%